Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health - Shishir, Mohammad Rezaul Islam; Saifullah, Md; Hashim, Sulafa B.H.; Aalim, Halah; Bilal, Muhammad; Khan, Suliman; Marappan, Gobinath; Tahir, Haroon Elrasheid; Zhihua, Li; Zhai, Xiaodong; Arslan, Muhammad; Taip, Farah Saleena; et al. (Elsevier B.V., 2024)
Yogurt is a popular dairy product due to its distinct taste and health-promoting effects. Nevertheless, yogurt has been fortified with different natural functional products, such as dietary fiber, micronutrients, probiotics, and bioactive phytochemicals, to improve the physicochemical, nutritional, and functional properties of the product. Numerous studies have explored yogurt fortification with unencapsulated functional ingredients over the last decade, but it affects yogurt quality and the stability of fortificants. Moreover, yogurt has precipitation issues with hydrophobic functional components. In recent years, researchers have shown a strong interest in micro and nano-encapsulation techniques to address these concerns about yogurt fortification. Micro and nanoencapsulation technologies have been discovered as a viable strategy for supplementing yogurt with essential nutrients, bioactive phytochemicals, probiotics, or a mixture of these. Therefore, this review focused on the impact of yogurt fortification using various micro and nano-encapsulated functional ingredients to improve product quality and prospective health advantages. Pickering emulsion, nanocomplexes, coated microbead, coated liposome, emulgel, emulsion bead, and multi-particulate dried microcapsule, were promising for the fortification of yogurt with natural products and improving the yogurt properties. The yogurt fortified with encapsulated natural products provided enhanced protection to encapsulated compounds during storage and gastrointestinal digestion and revealed better performance in the management of gut inflammation, anemia, obesity, tumorigenesis, and certain types of cancer. Recent studies explored that synbiotic microcapsule-fortified yogurts might show greater potential in maintaining the gut microenvironment through synergistic effects. To verify the effectiveness of fortified yogurts, more in vivo studies predominantly human clinical trials are recommended.